Contribution of San Fernando to scientific investigation. XVII-XIX centuries - Garmendia Lorena, Fausto (2021)
A retrospective bibliographic search on the history of the scientiphic research of the Faculty of Medicine of the Universidad Nacional Mayor de San Marcos (UNMSM), Lima-Perú, since XVII century until XIX century is done. In this order, bibliographic repositories SciELO, Scopus, Redalyc, PubMed, of the Universidad Peruana Cayetano Heredia as well as bachelors and doctoral thesis of UNMSM were revised, which were published in newspapers, medical scientiphic journals, and thesis to obtein original information on the matter. It was found a large bibliography that allows to point out that there was an increase in the medical publications since the begining of the Ilustration time, first in newspapers, in medical journals edited since 1827 to 1884 and medical thesis, mainly in the core subjects lines of health emblematic problems of Peru of that time. All of this allows to conclude that the information about health problems in Perú increased progresevely and in a more formal way since de Ilustration time until 1884.